Study the Effect of Scattering and Disperse Radiation on Equivalent Dose Rate for Al & Pb Shields (Baghdad Science Journal, 2011)
The effects of scattering and secondary radiation generated inside the material on dose equivalent rate where studied using Co60 and Cs137 sources of activity (199.8 , 177.6) MBq , respectively for different thicknesses of Al , Pb and Pb- glass . The results showed that the equivalent rate increases when the effect of scattering was included for Al and Pb shields with cobalt-60 source of energy 1.25 MeV ; and decreases for Pb shield with Cs-137 source of energy 0.662MeV .The results showed also that the atomic number of The material effects the dose equivalent rate . The Pb-glass shield was found to be more efficient in absorption than other shields.